Microencapsulated bio-based phase change material-micro concrete composite for thermal energy storage. (July 2021) - Parameshwaran, R.; Naresh, R.; Ram, V. Vinayaka; Srinivas, P.V.
Abstract: The quest and interest shown towards developing organic phase change materials (PCMs) for thermal energy storage (TES) applications in buildings are gaining momentum in recent years. From this perspective, the present study aims at developing a novel microencapsulated bio-based phase change material (MbP) integrated in to a micro concrete composite (MbPMC) for thermal energy storage in buildings. The MbP and MbPMC were experimentally characterized in terms of their morphological, thermal and structural properties. The surface morphology results signified that, the as-prepared MbP particles being formed were near-spherical in shape with sizes ranging between 2 μm and 10 μm. The highly crystalline nature of the bio-based PCM chains and the amorphous structure of the shell material were confirmed through the X-ray diffraction analysis. The Fourier transform infrared (FTIR) spectra has further confirmed the chemical stability between the core (PCM) and the shell material. The MbP has exhibited congruent phase change behavior with a good latent heat potential of 47.31 J/g. Besides, the MbP was found to be thermally stable, commencing from the operating temperature of 35 °C up to 150 °C, as confirmed through the leakage and thermogravimetric tests. A unique and optimized sequential operation of mixing the ingredients for preparing MbPMC matrix was established with a view to obtain the best end product. The as-prepared MbPMC has exhibited adequate structural integrity with a compressive strength of 38.78 MPa at a MbP dosage of 0.075% by the weight of cementitious materials added in the mix. Ultrasonic pulse velocities (UPV), along the directions orthogonal to the direction of pour of the concrete specimens, were observed to be very close, thus proving that the densities, across the cross section of the specimen are more or less uniform. For incremental dosages of MbP, the trend observed in the indicative compressive strengths of MbPMC specimens from rebound hammer tests was observed to be similar to the trend observed in the compressive strength values obtained from the compressive testing machine (CTM). In total, these test results have revealed the ability and stability of the MbP incorporated micro concrete composite (MbPMC) for achieving thermal energy storage and passive cooling in buildings without sacrificing its structural integrity. Graphical abstract: Image 1 Highlights: Novel microencapsulated bio-PCM (MbP) achieved improved thermal properties. MbP exhibited melting enthalpy of 47.3 kJ/kg and encapsulation efficiency of 26%. MbP possessed better leak proof abilities and thermal stability up to 150 °C. MbP infused micro concrete (MbPMC) resulted in adequate strength properties. MbPMC contained good thermal and structural properties desired for passive cooling.